The meanest doll in the world - Martin, Ann M., 1955-; Godwin, Laura; Selznick, Brian (New York : Hyperion Paperbacks for Children, 2005)
Annabelle and Tiffany, dolls living in the Palmer house, have an adventure when they hide in Kate Palmer's backpack, are carried to school, mistakenly go to another house, and try to stop a doll who is threatening all dollkind.
Originally published: New York : Hyperion Books for Children, 2003.
Sequel to: The doll people.
Keywords: Dolls -- Fiction; Self-perception -- Fiction; Human behavior -- Fiction